Managing Across or Within a Culture? Comparing Hotel Workers From China and Taiwan Using Hofstede’s Scales - Richard Metters; James Stanworth (Centre For Tourism Planning and Development, 2021)
Potential cultural differences between China and Taiwan are explored using Hofstede’s Values Survey Module (VSM94). The focus is on workers in hotels that cater to Western visitors. Hofstede’s VSM was administered to hotel workers in Tainan, Taiwan, and Shanghai, China. A comparison shows worker attitudes to be, in general, highly similar. Differences, however, on some scales, especially Power Distance, indicate that different managerial styles will be successful in the two countries. Qualitative data from industry stakeholders corroborate and elaborate on our findings.